Spiral-arm instability: giant clump formation via fragmentation of a galactic spiral arm. Issue 3 (21st November 2017) - Inoue, Shigeki; Yoshida, Naoki
Abstract: Fragmentation of a spiral arm is thought to drive the formation of giant clumps in galaxies. Using linear perturbation analysis for self-gravitating spiral arms, we derive an instability parameter and define the conditions for clump formation. We extend our analysis to multicomponent systems that consist of gas and stars in an external potential. We then perform numerical simulations of isolated disc galaxies with isothermal gas, and compare the results with the prediction of our analytic model. Our model describes accurately the evolution of the spiral arms in our simulations, even when spiral arms dynamically interact with one another. We show that most of the giant clumps formed in the simulated disc galaxies satisfy the instability condition. The clump masses predicted by our model are in agreement with the simulation results, but the growth time-scale of unstable perturbations is overestimated by a factor of a few. We also apply our instability analysis to derive scaling relations of clump properties. The expected scaling relation between the clump size, velocity dispersion, and circular velocity is slightly different from that given by the Toomre instability analyses, but neither is inconsistent with currently available observations. We argue that the spiral-arm instability is a viable formation mechanism of giant clumps in gas-rich disc galaxies.